Outcome of a Community-Based Oral Health Promotion Project on Primary Schoolchildren’s Oral Hygiene Habits - Heidi Halonen; Paula Pesonen; Liisa Seppä; Eija Peltonen; Leo Tjäderhane; Vuokko Anttonen (International Journal of Dentistry)
The aim of this study was to evaluate the effect of a school-based intervention project conducted in a mid-sized Finnish city, Laukaa on schoolchildren’s oral health behavior. Material and Methods. In the intervention, all children received dental education and some of the 7–12-year-old schoolchildren received individual tooth brushing instructions by a dental nurse in 2009-2010. Parents were present at the instruction sessions. In 2009 and 2010, all the children answered a questionnaire or an oral hygienist on their oral health behavior without identification. Results. Tooth brushing frequency increased significantly among the schoolchildren between the years 2009 (61.2%) and 2010 (65%) (); more so among younger children (7–10-year-olds) compared to the older ones (11-12-year-olds). The 2010 results showed a slight trend of decreasing tooth brushing frequency by age both among girls and boys. Younger children got significantly more often parental help or reminding. The girls brushed their teeth significantly more frequently (71.9%) than boys (57.0%). Conclusions. Our findings indicate that oral health intervention can be beneficial on health behavior especially for children at low grades. All children, 11 to 12 years of age, especially boys, need continuous health promotion.